Occurrence and Distribution of Tetracycline Antibiotics and Resistance Genes in Longshore Sediments of the Three Gorges Reservoir, China - Lu, Lunhui; Liu, Jie; Li, Zhe; Liu, Zhiping; Guo, Jinsong; Xiao, Yan; Yang, Jixiang (Frontiers in Microbiology, 2018)
.The widespread use of antibiotics and the induced antibiotic resistance genes have attracted much attention in recent years. The longshore sediments in the water-level-fluctuating zone of the Three Gorges Reservoir were selected to investigate the spatial-temporal distribution of antibiotics and antibiotic resistance genes in two different operation stages (low-water level in summer and high-water level in winter). Three kinds of tetracycline antibiotics (tetracycline, oxytetracycline and chlortetracycline) and three kinds of tetracycline resistance genes (tet(A), tet(C), tet(M)) were analyzed and quantified. The results showed that the distribution of tetracyclines and resistance genes in riverine, transition and lacustrine zones showed a certain regularity, and the tetracycline antibiotics concentration and the total abundance of the tetracycline resistance genes were highest in the transition zone, and then the riverine zone. Meanwhile, there were significant seasonal variations of tetracycline and the resistance genes. The concentrations of the tetracycline and resistance genes were higher in summer than those in winter, while the relative abundance of resistance genes was higher in winter. It was suggested that the different seasonal distribution of antibiotics and resistance genes may be correlated with the reservoir operation in the Three Gorges Reservoir and the higher use of antibiotics in winter. In addition, Pearson correlation analysis showed that the concentrations of the tetracycline, class 1 integron and 16S rRNA were positively correlated with the abundance of the tetracycline resistance genes.